Private Higher Education in Brazil: Fueling Economic Growth - Bezerra, José Janguiê; Niskier, Celso; Batourina, Lioudmila (International Higher Education, 2017)
The Brazilian private education sector is one of the largest in the world. Today there are more than 6 million students enrolled in private higher education institutions, which represents more than 75 percent of all university students. Brazilian higher education started expanding in 1996, when the government, according to the National Education Plan, introduced a fund allowing young people to take up students loans. From 1996 to 2010, the government took a number of actions, addressing the problem of social inclusion and supplying the country with educated, middle class workers. The Brazilian Association of Private Universities (ABMES—Associação Brasileira de Mantenedoras de Ensino Superior) is pushing the government to keep investing in the scholarships in spite of the economic crisis, and working together on finding alternative funding mechanisms to provide society with access opportunities to higher education, and to sustain economic growth.